Effect of fiber dosage and prestress level on shear behavior of hybrid GFRP-steel reinforced concrete I-shape beams without stirrups - Soltanzadeh, Fatemeh (2016)
Corrosion of steel reinforcements embedded in concrete elements is generally known as one of the most common reasons that shorten the service life of the structures. The present study aims to contribute in overcoming this problem by replacing steel stirrups as shear reinforcement of concrete beams using a steel fiber reinforced self-compacting concrete (SFRSCC). In the present research the potential of SFRSCC for improving the shear resistance of the beams without stirrups is explored. In order to further reduce the risk of corrosion in this type of beams, a hybrid system of flexural reinforcement composed of a steel strand and GFRP rebars is applied and properly arranged in order to assure a relatively thick concrete cover for the steel reinforcement. The GFRP bars are placed with the minimum cover thickness for providing the maximum internal arm and, consequently, mobilizing efficiently their relatively high tensile strength. The effectiveness of applying different dosages of steel fibers and varying the prestress force to improve the shear behavior of the designed beam are evaluated. By considering the obtained experimental results, the predictive performance of a constitutive model (plastic-damage multidirectional fixed smeared crack model) implemented in a FEM-based computer program, as well as the one from three analytical formulations for estimating shear resistance of the developed beams were assessed. The FEM-based simulations have provided a good prediction of the deformational response and cracking behavior of the tested beams. All the analytical formulations demonstrated acceptable accuracy for design purposes, but the one proposed by CEB-FIP Modal Code 2010 predicts more conservative shear resistance.